2020
DOI: 10.3389/fnins.2020.588515
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography Reveals Distinct Retinal Structural and Microvascular Abnormalities in Cerebrovascular Disease

Abstract: Cerebrovascular disease (CeVD) is one of the leading global causes of death and severe disability. To date, retinal microangiopathy has become a reflection of cerebral microangiopathy, mirroring the vascular pathological modifications in vivo . To evaluate the retinal structure and microvasculature in patients with CeVD, we conducted a cross-sectional study in Zhongshan Ophthalmic Center and Department of Neurology of Third Affiliated Hospital, Sun Yat-sen University using optical cohere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…There are increasing evidences that the retina can reflect cerebrovascular and systemic vascular alterations ( 11 13 ). The retinal and cerebral microvasculature share physiological and morphological characteristics; therefore, the clinical assessment of retinal vessels could be a potential marker of the state of the cerebrovasculature.…”
Section: Introductionmentioning
confidence: 99%
“…There are increasing evidences that the retina can reflect cerebrovascular and systemic vascular alterations ( 11 13 ). The retinal and cerebral microvasculature share physiological and morphological characteristics; therefore, the clinical assessment of retinal vessels could be a potential marker of the state of the cerebrovasculature.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, OCT studies found that retinal neural damage occurs with microvascular rarefication 28 . The cerebrovascular disease can be identified for its distinct neurovascular alteration pattern on the retina 40 . Hence, further exploration is required to uncover the specificity of OCTA on detecting CVDs fully.…”
Section: Discussionmentioning
confidence: 99%
“…OCTA imaging was performed using an ultra‐clear OCT and AngioPlex device (Cirrus 5,000, version 10.0; Zeiss Meditec, California, USA) as described previously. (Zhang, Xiao, Liu, Liu, et al., 2020; Zhang, Xiao, Liu, Zhao, et al., 2020) Briefly, we selected an optic disc cube 200 × 200 scan protocol for pRNFL measurements. pRNFL thickness was measured within 3.46‐mm‐diameter circles around the optic disc.…”
Section: Methodsmentioning
confidence: 99%